2002
DOI: 10.1080/0049825021000017902
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolism of diallyl disulphide in the rat: identification of two new metabolites

Abstract: 1. Diallyl disulphide (DADS), a compound formed from the organosulphur compounds present in garlic, is known for its anticarcinogenic effects in animal models. 2. The aim was to identify and analyse the metabolites produced in vivo after a single oral administration of 200 mg kg(-1) DADS to rats. The organic sulphur metabolites present in the stomach, liver, plasma and urine were measured by gas chromatography coupled with mass spectrometry over 15 days. 3. Data indicate that DADS is absorbed and transformed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 21 publications
6
54
0
Order By: Relevance
“…The cytotoxic effects of DAS have been reported to occur at concentrations ranging from 150 to 500 g/ml, and several other studies have shown that lower concentrations (5 to 100 M) of the compounds have no cytotoxic effect (3,10,25,31). The antimicrobial effects observed in our study were found at a concentration of 0.01 g/ml.…”
Section: Discussionsupporting
confidence: 70%
“…The cytotoxic effects of DAS have been reported to occur at concentrations ranging from 150 to 500 g/ml, and several other studies have shown that lower concentrations (5 to 100 M) of the compounds have no cytotoxic effect (3,10,25,31). The antimicrobial effects observed in our study were found at a concentration of 0.01 g/ml.…”
Section: Discussionsupporting
confidence: 70%
“…DADS is also partially converted to allyl mercaptan in the blood before reaching the liver or other organs, and is transformed into other products including allyl methyl sulfi de, allyl methyl sulfoxide and allyl methyl sulfone (30)(31)(32). Thus, it is conceivable that these metabolic products affect the number of lymphocytes and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms, first proposed by Block (1985), for the formation of AA in aqueous environments such as those found in vivo result from the transformation of the thiosulphinates such as diallyl trisulphide and diallyl disulphide (Block, 1985;Block et al, 1992), with up to one-third of the 'lost' allyl groups during the transformation producing AA (Lawson, 1996). Recent investigations with rats reported that similar degradative metabolites are formed in vivo (Germain et al, 2002).…”
Section: Introductionmentioning
confidence: 99%